Pengembangan model pembelajaran tematik integratif penjasorkes berbasis permainan siswa sekolah dasar - Agung Widodo (Jurnal Pendidikan Jasmani Indonesia, 2017)
Penelitian ini bertujuan untuk menghasilkan model pembelajaran tematik integratif Penjasorkes berbasis permainan bagi siswa sekolah dasar kelas 1 Kecamatan Gantiwarno Klaten. Penelitian ini merupakan penelitian dan pengembangan yang terdiri atas dua tahapan yaitu tahap penelitian pendahuluan terdiri dari kajian literatur, kajian penelitian relevan, studi lapangan dan tahap pengembangan terdiri perencanaan, validasi ahli, uji skala kecil, dan uji skala besar. Validasi melibatkan 3 orang ahli. Uji skala kecil dilakukan terhadap 16 siswa kelas 1 dan 2 orang guru di sekolah dasar Muhammadiyah Gantiwarno. Uji skala besar dilakukan terhadap dua kelas yang masing-masing terdiri dari 26 siswa kelas 1 dan 3 orang guru di sekolah dasar Muhammadiyah Gantiwarno dan sekolah dasar Negeri Ngandong 2. Hasil penelitian berupa model pembelajaran tematik integratif Penjasorkes berbasis permainan bagi siswa sekolah dasar kelas 1 Kecamatan Gantiwarno Klaten. Model disusun dalam buku petunjuk dengan judul “model permainan integratif bagi siswa sekolah dasar kelas 1”. Berdasarkan penilaian para ahli, isi materi sangat baik, bahasa sangat baik, dan format penulisan sangat baik. Berdasarkan uji skala kecil dan besar secara substansi dan pelaksanaan tergolong sangat baik. Developing a thematic integrative learning model of physical education based on games for students of elementary school  AbstractThis research aims to develop a thematic integrative learning model of physical education based on games for students of grade 1 elementary school in Gantiwarno Klaten District. This study is a research and development which consists of two stages: preliminary research stage consisted of a literature review, a review of relevant research, field studies and stage of development consisted of planning, expert validation, small-scale testing and large-scale testing. The validation involved three experts. The trials were conducted in a small-scale with 16 students in grade 1 and two teachers in Elementary School Muhammadiyah Gantiwarno. The large-scale trials were conducted with two classes, each consisting of 26 students in grade 1 and three teachers in Elementary School Muhammadiyah Gantiwarno and State Elementary School 2 Ngandong. The results of the study are in the form of a thematic integrative learning model of physical education based on games for students of elementary school grade 1 in Gantiwarno Klaten Districts. The model is arranged in the guidebook with the title “an integrative model of the game for primary school students in grade 1”. Based on the assessment of the experts, this guidebook has a very good content material, very good language, and very good writing format. Based on the small-scale and large-scale test, the substance is classified as very good and its implementation is quite very good.